Sleep disorders and other medical and socio-demographic factors in systemic scleroderma - Leyla Bagheri; Hoda Kavosi; Nasim Shokouhi; Shila Aghayani; Khosro Sadeghniiat Haghighi; Seyed Reza Najafizadeh (PAGEPress Publications, 2024)
We aimed to investigate sleep disorders in patients with systemic scleroderma (SSc) and its relationship with socio-demographic and medical factors and to provide a suitable solution to better control the disease and improve the quality of life in these patients. This cross-sectional study evaluated SSc patients seen at a rheumatology clinic from September 1, 2022, through April 1, 2023.The patients were examined by the main investigator of the project and entered the study after taking the medical history and meeting the criteria of ACR 2013 Classification Criteria. Pittsburgh Sleep Quality Index (PSQI), Insomnia Severity Index (ISI), Epworth Sleepiness Scale (ESS) and STOP-Bang Questionnaire were employed to investigate sleep disorders. A total of 103 patients were included in the study. The average age of the patients was 48.42 ± 12.4 years. PSQI showed lower quality of sleep scores among SSc (68% of patients), which was significantly related to the degree of skin stiffness in patients, telangiectasia, interstitial lung disease (ILD) in computed tomography (CT) scan, patient age, duration of the disease, and pulmonary artery pressure (PAP). STOP-Bang Questionnaire revealed that obstructive sleep apnea (OSA) was significantly associated with telangiectasia, ILD, patient age, disease onset age, disease duration, body mass index and PAP. Insomnia had a statistically significant relationship with telangiectasia, ILD and patient age. Drowsiness during daily activities was not significantly related to any of the individual variables and disease-related variables. Sleep disorders are common in patients with systemic scleroderma. Telangiectasia, ILD and patient age were related to all sleep quality disorders and respiratory apnea and insomnia. Furthermore, the amount of skin involvement significantly causes disturbances in the quality of sleep of patients, where in the group with diffuse skin stiffness, 80% of patients exhibited disturbances in the quality of sleep. Therefore, paying attention to sleep health can be an effective factor in improving the quality of life of patients with SSc.